Optimizing the Implementation of an Electronic-Based Government System (SPBE) in Overseas Official Travel Permits in Higher Education - Aas Rohmat; Muhammad Muhtarom; Ismiyanto Ismiyanto; Evi Elisanti; Anies Fortina Febriani (Universitas Sebelas Maret, 2024)
The research aims to determine the optimization of the implementation of an electronic-based government system (SPBE) in licensing overseas official travel for state civil servants in higher education. The research method used is descriptive qualitative. The normative legal approach is research that examines document studies using various secondary data. The research location is at one of the universities in the city of Solo. Data collection techniques are carried out using literature studies, observation, interviews, and documentation through field observations as research objects. Data analysis in this research uses qualitative analysis techniques. The research results show that optimizing the implementation of an electronic-based government system requires an appropriate policy framework, so that the SPBE vision can be achieved. SPBE is expected to be able to realize an integrated work process that is effective, efficient, and improves the quality of public services on overseas official trips at universities. The development of SPBE can increase ASN human resources in mastering information and communication technology both in quality and quantity so that overseas official travel services are optimal for state civil servants in higher education. The conclusion of this research is to maximize or minimize achieving a goal precisely, effectively, efficiently, and beneficially in implementing an Electronic-Based Government System (SPBE) during overseas official trips.